If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b(2b + 1) = 36 Reorder the terms: b(1 + 2b) = 36 (1 * b + 2b * b) = 36 (1b + 2b2) = 36 Solving 1b + 2b2 = 36 Solving for variable 'b'. Reorder the terms: -36 + 1b + 2b2 = 36 + -36 Combine like terms: 36 + -36 = 0 -36 + 1b + 2b2 = 0 Factor a trinomial. (-9 + -2b)(4 + -1b) = 0Subproblem 1
Set the factor '(-9 + -2b)' equal to zero and attempt to solve: Simplifying -9 + -2b = 0 Solving -9 + -2b = 0 Move all terms containing b to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2b = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2b = 0 + 9 -2b = 0 + 9 Combine like terms: 0 + 9 = 9 -2b = 9 Divide each side by '-2'. b = -4.5 Simplifying b = -4.5Subproblem 2
Set the factor '(4 + -1b)' equal to zero and attempt to solve: Simplifying 4 + -1b = 0 Solving 4 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1b = 0 + -4 -1b = 0 + -4 Combine like terms: 0 + -4 = -4 -1b = -4 Divide each side by '-1'. b = 4 Simplifying b = 4Solution
b = {-4.5, 4}
| 1/2(x+2)(3x-14)=(x+2)(x+2) | | 4x^2+18x+24=0 | | 2(t+3)=t(t+7) | | -55+X=100 | | 5-2(x-1)=4-x | | 5(3y-4)-3(2y+1)= | | x+(-47)=-37 | | 10x+15=12x-1 | | 52/12-17/10+3/4 | | 7x+3=30-2x | | 7/12k=I | | 3x-18=3*1 | | 7x+3=20-2x | | 2t^2+2t-2=0 | | 2(3x-4)+2=42 | | 2x-3=-20x | | 2x-3=-20 | | 2x-3=4*2 | | =15+273.15 | | 8000/4 | | X+(X*0.05)=1068 | | 5x+8=60-125x | | (2x-1)=3(x+7) | | 9x+7y+17z=107 | | 4-(15-2x)=3(2x-9-2(9-x)) | | 4x^2-3x+12=0 | | 60x+1=3(3+4x) | | 60x+10=80x-6 | | 36=2l+2w | | -21=7+6(c+5) | | 10x+1=12x-17 | | -6(7-9x)=-21 |